Salafi Madrasa, Nation, and (Pseudo-) Nationalism: A Case Study of Two Islamic Education Institutions in Indonesia - Wahyu Mulyadi; Sangkot Sirait; Sabarudin Sabarudin (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
This research aims to examine the negotiations between two Islamic movement organizations, Salafi and Jamaah Ansharus Syariah (JAS), as conservative Islamic movements whose main goal is to return to the original sources of Islam, the Qur'an and As-Sunnah. This study uses a qualitative descriptive research design with data collection methods through observation, interactive interviews, and documentation conducted in two educational institutions owned by Salafi and JAS, using primary and secondary data sources. The research findings are as follows. First, it shows that Salafi and JAS, as fundamentalist movement groups, are capable of conducting cooperative negotiations using the concept of political agonism. Second, the negotiation process of Salafi and JAS emphasizes the concept of nationalism for the sake of the operational interests of educational institutions. Third, Salafi and JAS develop their movement ideology among students and their parents. This research portrays the existence of Pseudo Nationalism, positioning themselves in a contemporary style and acting as an anchor for balance, thereby impacting the existence and strengthening of their ideology.